EPIGENETICS OF HUMAN COGNITIVE PERFORMANCE - dos Santos Neto, Oriel Pereira; Umeno, Guilherme Minaro Costa; Santos, Kayo Phelipe de Melo; Martins, Júlio Carneiro Vieira; Reis, Miguel Ferro; Tavares, Alessandra de Castro; Silva, Antonio Márcio Teodoro Cordeiro (Seven Editora, 2025)
This article has as its objects of study the epigenetic factors involved in the expression of human cognition and seeks to offer a compilation of scientific knowledge about the epigenetic aspects associated with cognitive manifestation. In the meantime, a literature review was carried out with the collection of 21 articles produced between 2018 and 2024, which present as main findings the facts that, from epigenetic modifications, caused by environmental factors, in the patterns of methylation, acetylation, histones, and miRNA expression, impacts on individual intellectual expression are observed that may be directly or indirectly related to these epigenetic mechanisms or to neurological pathologies such as Alzheimer’s. Therefore, with the understanding of these cognitive factors, there is the core for research on therapies aimed at cognitive maintenance with aging. DOI: https://doi.org/10.56238/sevened2024.037-203